Optimalisasi Efisiensi Biaya: Studi Kasus Analisis Rasio Biaya Dana Bank BNI Pada Tahun 2019-2023 - Desita Fitriani; Leira Narulita; Muhammad Aditya Darmawan; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to analyze the cost of funds ratio as an indicator of cost efficiency in banking operations, with a focus on Bank BNI. The banking industry plays a vital role in the economy by providing financial services to individuals, businesses and governments. In a global context, banks must adapt to market, technological and regulatory changes to remain relevant and profitable. Cost efficiency is the key to successful bank operations. A case study on Bank Negara Indonesia (BNI) shows fluctuations in the cost of funds ratio, cost of loanable funds, and cost of money over the 2019-2023 period. The implications highlight the importance of efficient fund management to improve profitability and the continuity of bank operations. The conclusion of this study provides direction to improve fund management and the overall financial performance of the bank.